Application of optical fiber distributed sensing to health monitoring of concrete structures - Villalba, Sergi; Casas, Joan R. (Mechanical systems and signal processing, 2013)
The use of Optical Backscatter Reflectometer (OBR) sensors is a promising measurement technology for Structural Health Monitoring (SHM) as it offers the possibility of continuous monitoring of strain and temperature along the fiber. Several applications to materials used in the aeronautical construction have demonstrated the feasibility of such technique. These materials (composites, steel, aluminum) apart from having a smooth surface where the bonding of the sensor is easily carried out, they also have a continuous strain field when subject to external loading and therefore the bonding of the OBR on the material surface is not in danger for high levels of loading as the OBR can easily follow the strain in the material. The application of such type of sensor to concrete structures may present some difficulties due to (1) the roughness of the concrete surface and the heterogeneity due to the presence of aggregates of several sizes, (2) the fact that reinforced concrete cracks at very low level of load, appearance of a discontinuity in the surface and the strain field that may provoke a break or debonding of the optical fiber. However the feasibility of using OBR in the SHM of civil engineering constructions made of concrete is also of great interest, mainly because in this type of structures it is impossible to know where the crack may appear and therefore severe cracking (dangerous for the structure operation) can appear without warning of the monitoring if sensors are not placed in the particular location where the crack appears. In order to explore the potentiality of detecting cracks as they appear without failure or debonding, as well as the compatibility of the OBR bonding to the concrete surfaces, this paper shows the test carried out in the loading up to failure of a concrete slab. ► OBR sensors offer a continuous monitoring of strain and temperature along the fiber. ► They can be easily placed on a concrete surface despite the existing roughness. ► OBR sensor is capable to detect appearance of cracks that are hardly visible. ► Optical fiber OBR frequency signals are acquired properly and these provide strain values without breaks of the sensor. ► The effectiveness of the OBR sensors is confirmed.